In case you're not already aware, the expression
is called the "difference quotient" and represents the average rate of change of a function
over an interval
.
For the function
, by substituting
we get
![f(x+h)=(x+h)^2+3(x+h)+4=(x^2+2xh+h^2)+(3x+3h)+4=x^2+3x+4+(2x+3)h+h^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ozgjthhqidfhf7sz578y0er51vg8m55uuj.png)
Then the difference quotient is
![\frac{f(x+h)-f(x)}h=\frac{(x^2+3x+4+(2x+3)h+h^2)-(x^2+3x+4)}h](https://img.qammunity.org/2021/formulas/mathematics/middle-school/903f8p087hq49bky94blcq9bjv2leu1ewr.png)
![=\frac{(2x+3)h+h^2}h=2x+3+h](https://img.qammunity.org/2021/formulas/mathematics/middle-school/57wv0q6lnj9tk9a2d776p0icbtxgyrybbp.png)
where the last equality holds as long as
.